Comportamiento Organizacional en la Asociación de Servicios de Limpieza Babahoyo Limpio (ASOSERLIMBA) - Peñafiel Cegido, Gearnelly Marian (2020)
This case study aims to present the analysis of organizational behavior in the Babahoyo Limpio Cleaning Services Association and its effect on the performance of the organization by identifying the structure of the organization, the attitudes and behaviors of the groups and their relationship with the correct management of interpersonal relationships in the workplace and how it intervenes in the commitment that the employee has to achieve the organizational objectives of the association. The methodology used was based on a quantitative study, carried out through the application of individual surveys and interviews that allowed the results to be analyzed and presented. Under the inductive method, it is established to reach general conclusions based on particular reasoning, such as behavior at the level group observed in the analysis unit presents a conflictive work environment and individualistic business culture and reforms in the organizational structure for better management. The study of organizational behavior serves to manage people in organizations of any kind.